CD44v6+ Hepatocellular Carcinoma Cells Maintain Stemness Properties through Met/cJun/Nanog Signaling. (7th November 2022) - Chen, Wei; Wang, Ronghua; Zhao, Yuchong; Li, Yawen; Wang, Xiju; Peng, Wang; Bai, Shuya; Zheng, Mengli; Liu, Man; Cheng, Bin
Abstract : Cancer stem cells (CSCs) are characterized by their self-renewal and differentiation abilities. CD44v6 is a novel CSC marker that can activate various signaling pathways. Here, we hypothesized that the HGF/Met signaling pathway promotes stemness properties in CD44v6+ hepatocellular carcinoma (HCC) cells via overexpression of the transcription factor, cJun, thus representing a valuable target for HCC therapy. Magnetic activated cell sorting was used to separate the CD44v6+ from CD44v6- cells, and Met levels were regulated using lentiviral particles and the selective Met inhibitor, PHA665752. An orthotopic liver xenograft tumor model was used to assess the self-renewal ability of CD44v6+ cells in immunodeficient NOD/SCID mice. Luciferase reporter and chromatin immunoprecipitation assays were also conducted using cJun-overexpressing 293 T cells to identify the exact binding site of cJun in the Nanog promoter. Our data demonstrate that CD44v6 is an ideal surface marker of liver CSCs. CD44v6+ HCC cells express higher levels of Met and possess self-renewal and tumor growth abilities. Xenograft liver tumors were smaller in nude mice injected with shMet HCC cells. Immunohistochemical analysis of liver tissue specimens revealed that high Met levels in HCC cells were associated with poor patient prognosis. Further, a cJun binding site was identified 1700 bp upstream of the Nanog transcription start site and mutation of the cJun binding site reduced Nanog expression. In conclusion, the HGF/Met signaling pathway is important for maintenance of stemness in CD44v6+ HCC cells by enhancing expression of cJun, which binds 1700 bp upstream of the Nanog transcription start site.